Language shift in Newar: a case study in the Kathmandu Valley - Gautam, Bhim Lal (Nepalese Linguistics, 2018)
This paper explores the patterns of language shift in Newar, the ethnic indigenous language community living in the Kathmandu Valley. The research focuses on language contact situations in different domains viz. social, cultural, personal, and official as well as media related activities where the informants are asked to use different languages along with the use of their own mother tongue i.e. Newar. This socio-ethnographic research aims at providing some clues as to how the discovery of a minority language triggers changes in representations and attitudes.